TEXTBOOK EVALUATION ON EVERYDAY ENGLISH FOR HOSPITALITY PROFESSIONALS AND ENGLISH FOR WORK IN EFL CLASSROOM - Sahyoni Sahyoni (SALEE: Study of Applied Linguistics and English Education, 2020)
Textbook plays important role in teaching English. Yet, not all textbook is appropriately meet to the students’ needs and knowledge level. The material for EFL is totally different to Native speaker of English. One of the ways matching students’ needs and textbook is by doing textbook evaluation. This research is aimed at discussing textbooks that are used by the teacher in English Foreign Language (EFL). The textbooks that have been chosen are English for Everyday English for Hospitality Professionals by Lawrence, J. Zwier and Nigel Caplan (2007) and English for Work (2003) by Ian Badger. Both of them are ESP textbooks where they are taught in a foreign language class. The purpose of this research is to know how much Everyday English for Hospitality Professionals and English for Work textbook used in college meets the criteria of good EFL textbook. The research design is a descriptive-evaluative. The procedure of analyzing the data starts by analyzing the data based on EFL evaluation criteria, then finding out how much each items meet the criteria of good EFL textbook and concluding the result. The research result revealed that most parts of the textbooks are appropriately met to the students’ needs. Most of the material stated inside of the textbooks covered students’ knowledge level and relevant for the field of study. Keywords: evaluation, foreign learner class, textbooks